On dispersed native metal particles in black shales of the euxinic type – megatraps of natural gas - Lukin, А. Е.; Sаmоylеnко, I. I. (Reports of the National Academy of Sciences of Ukraine, 2015)
Black shales – euxinites (specific lithogeodynamic indicators of the sediments of back-arc basins) are contaminated with chemically and morphologically different dispersed native-metallic micro- and nano-particles – the tracers of (super)deep fluids.